Barriers to Occupational Health and Safety Legal Services During Pandemic - Arjun Aryal; Ava Shrestha; Yadav Prasad Joshi (The Journal of Medicine, Law & Public Health)
Objectives: This study aimed to identify the barriers to accessing legal services related to occupational health and safety during the COVID-19 pandemic.